Application Of Deep Foundation Structures To Great Bridges In Vietnam - Cau T. Bui (Deep Foundations Institute, 2008)
Thanks to Doi-moi (renovation) policy, many great bridges were constructed in Vietnam to meet demands of her booming economy in the recent decade and deep foundation structures were the only alternatives for the foundations of these great bridges. The deep foundation structures were constructed by modern technologies and almost of all these deep foundation structures were designed by foreign companies and carried out by Vietnamese workers and engineers under supervision of foreign experts. Beside successes, there were several failure cases in which the collapse of temporary scaffolding system of Can-tho Cable ? Stayed Bridge due to settlement of its pile foundation killing 54 workers and seriously injuring 80 other workers was the most serious. This paper introduces construction techniques of the deep foundation structures applied to building of great bridges in Vietnam recently. It will especially focus on two failure cases: 1) collapse of temporary scaffolding system of Can-tho Cable ? Stayed Bridge due to settlement of its pile foundation and 2) failure of drilled shaft foundation of Thanh-tri bridge due to poor construction technique and management. These two failure cases were greatly concerned by both bridge specialists and the public. Reasons of and lessons from these two failure cases will be carefully discussed. From the two failure cases, this paper will draw some lessons that should be important issues to be seriously paid attention when designing and constructing deep foundations in Vietnam.